2005
DOI: 10.1002/jcp.20408
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin prevents methylglyoxal‐induced oxidative stress and apoptosis in mouse embryonic stem cells and blastocysts

Abstract: Methylglyoxal (MG) is a reactive dicarbonyl compound endogenously produced mainly from glycolytic intermediates. Elevated MG levels in diabetes patients are believed to contribute to diabetic complications. MG is cytotoxic through induction of apoptosis. Curcumin, the yellow pigment of Curcuma longa, is known to have antioxidant and anti-inflammatory properties. In the present study, we examined the effect of curcumin on apoptotic biochemical events caused by incubation of ESC-B5 cells with MG. Curcumin inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
107
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(116 citation statements)
references
References 48 publications
8
107
0
1
Order By: Relevance
“…Severe dicarbonyl stress also induces decreased cell growth and viability -as we and others have found previously in ESCs, other cell types, mouse oocytes, fertilization, and fetal development [52][53][54]. Mild dicarbonyl stress was induced by mESC culture in 3% oxygenthrough down regulation of Glo1 expression and increased anaerobic glycolysis with increased flux of formation of MG.…”
Section: Discussionsupporting
confidence: 71%
“…Severe dicarbonyl stress also induces decreased cell growth and viability -as we and others have found previously in ESCs, other cell types, mouse oocytes, fertilization, and fetal development [52][53][54]. Mild dicarbonyl stress was induced by mESC culture in 3% oxygenthrough down regulation of Glo1 expression and increased anaerobic glycolysis with increased flux of formation of MG.…”
Section: Discussionsupporting
confidence: 71%
“…have not yet been clearly defined, studies have shown that caspase activation, MMP (mitochondrial membrane potential) changes and JNK (c-Jun N-terminal kinase) activation are critical for the mitochondria-dependent apoptotic pathway [9,14]. In addition, previous studies have shown that some apoptotic stimuli trigger heat-shock responses, such as activation of the HSPs (heat-shock proteins), which are molecular chaperones that rescue damaged proteins by facilitating their refolding [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, apoptotic processes do not occur prior to the blastocyst stage during normal mouse embryonic development [8], and induction of apoptosis during the early stages of embryogenesis (i.e. by exposure to a teratogen) has been shown to cause embryonic developmental injury [9,10]. Many of the chemical and physical treatments that induce apoptosis stimulate oxidative stress via generation of ROS (reactive oxygen species) [9,[11][12][13], suggesting a close relationship between oxidative stress and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that transforming growth factor ␣ protects ICM from apoptosis [3,4]. Cultured mouse embryonic stem (mES) cells derived from ICM undergo apoptosis when subjected to prolonged hypoxia or methylglyoxal-induced oxidative stress [5,6]. However, little is known about the endogenous protective mechanism.…”
Section: Introductionmentioning
confidence: 99%